2016
DOI: 10.2215/cjn.04770415
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Genetic, and Urinary Factors Associated with Uromodulin Excretion

Abstract: Background and objectives The urinary excretion of uromodulin is influenced by common variants in the UMOD gene, and it may be related to NaCl retention and hypertension. Levels of uromodulin are also dependent of the renal function, but other determinants remain unknown.Design, setting, participants, & measurements We tested associations between the urinary excretion of uromodulin; medical history and medication; serum and urinary levels of electrolytes, glucose, and uric acid; and the genotype at the UMOD/Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 46 publications
4
32
1
1
Order By: Relevance
“…There were several other interesting findings from the Canadian study (2). Consistent with prior studies, uromodulin excretion was significantly higher in individuals with the rs4293393T variant.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…There were several other interesting findings from the Canadian study (2). Consistent with prior studies, uromodulin excretion was significantly higher in individuals with the rs4293393T variant.…”
supporting
confidence: 85%
“…Two new publications (1,2) in this issue of the Clinical Journal of the American Society of Nephrology (CJASN) further add to this knowledge. In this editorial, we will review recent developments in this area and provide a context for the two new investigations.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Finally, a number of studies have shown that uromodulin levels are affected by UMOD polymorphisms. 31,32 While the focus of this study was not on uromodulin genotype, further studies need to evaluate if uromodulin genotype is associated with clinical UTI in humans.…”
Section: Discussionmentioning
confidence: 99%